2010
DOI: 10.1152/ajpcell.00047.2010
|View full text |Cite
|
Sign up to set email alerts
|

Tetracyclines: a pleitropic family of compounds with promising therapeutic properties. Review of the literature

Abstract: There must be something unique about a class of drugs (discovered and developed in the mid-1940s) where there are more than 130 ongoing clinical trials currently listed. Tetracyclines were developed as a result of the screening of soil samples for antibiotic organisms. The first of these compounds chlortetracycline was introduced in 1948. Soon after their development tetracyclines were found to be highly effective against various pathogens including rickettsiae, Gram-positive, and Gram-negative bacteria, thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
298
0
18

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(318 citation statements)
references
References 92 publications
2
298
0
18
Order By: Relevance
“…The best characterized non-antimicrobial property of the doxycycline is its ability to inhibit members of the MMP family of endopeptidases [12], many of which are largely up-regulated in the setting of animal [19][20][21] and human [22,23] hearts after MI. Previous studies have also shown that doxycycline has some ability to inhibit reactive oxygen species (ROS) [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best characterized non-antimicrobial property of the doxycycline is its ability to inhibit members of the MMP family of endopeptidases [12], many of which are largely up-regulated in the setting of animal [19][20][21] and human [22,23] hearts after MI. Previous studies have also shown that doxycycline has some ability to inhibit reactive oxygen species (ROS) [24].…”
Section: Discussionmentioning
confidence: 99%
“…Several pleiotropic properties of doxycycline related mainly to its ability to act as metalloproteinases (MMPs) inhibitor can explain these beneficial effects [12].…”
mentioning
confidence: 99%
“…Algunos estudios han descrito, que a altas dosis el uso de doxiciclina puede bajar la tasa de filtración glomerular causando estados de isquemia en la arteriola eferente que puede llegar a inducir el incremento en los valores de creatinina sérica, una de las teorías es la reducción en el estrés oxidativo, disminuyendo los niveles de citoquinas e inhibición de la actividad de metaloproteinasas de matriz (5,30). Se ha determinado en diferentes estudios las propiedades antiinflamatorias e inmunomoduladoras de la doxiciclina asociadas a estos efectos (31,32).…”
Section: Ehrlichia Canis and The Effects Of Doxycycline In The Treatmentunclassified
“…One of the theories is the reduction of the oxidative stress, decreasing cytokine levels and inhibiting the activity of matrix metalloproteinases (5,30). The anti-inflammatory and immunomodulatory properties of doxycycline associated with these effects have been determined in different studies (31,32). …”
Section: Sistema Inmunementioning
confidence: 99%
“…Por lo tanto, las tetraciclinas, además de inhibir estas metaloproteasas, también impiden su producción, ya que interfieren en la activación proteolítica de pro-MMP, mediante la quelación de zinc en la zona de unión con la enzima, bloqueando la actividad de MMPs. Particularmente, se ha demostrado que la doxiciclina (figura 1) es más efectiva que la minociclina en la inhibición de MMPs (García-Álvarez & Oteo, 2010;Griffin, Fricovsky, Ceballos & Villarreal, 2010).…”
Section: Tetraciclinasunclassified